2011
DOI: 10.3892/ijmm.2011.598
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-155 regulates angiotensin II type 1 receptor expression in umbilical vein endothelial cells from severely pre-eclamptic pregnant women

Abstract: Abstract. Angiotensin II is critical in pre-eclampsia pathogenesis. In addition, microRNA-155 regulates angiotensin II type 1 receptor expression. We have explored the function of microRNA-155 in pre-eclamptic pregnant women. Human umbilical vein endothelial cells were isolated and cultured from healthy puerperant women and pre-eclampsia patients. The cells were transfected with a mature microRNA-155 plasmid. The effect of microRNA-155 was assessed by Northern blotting, in situ hybridization, quantitative real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Later, Zhang et al (2010) found a similar trend in miR-155 greatly upregulated in preeclampsia placenta. By contrast, Cheng et al (2011) demonstrated that severely preeclamptic pregnant women had less mature miR-155, yet a much higher expression of AT1R in their human umbilical vein endothelia cells (HUVECs) compared with healthy puerperant women. Similarly, a recent study indicated that overexpression of miR-155 in HUVECs (Zhu et al 2011) suppressed the expression of AT1R via interacting (Xu et al 2008).…”
Section: Mirna Related To Raas In Preeclampsiamentioning
confidence: 95%
“…Later, Zhang et al (2010) found a similar trend in miR-155 greatly upregulated in preeclampsia placenta. By contrast, Cheng et al (2011) demonstrated that severely preeclamptic pregnant women had less mature miR-155, yet a much higher expression of AT1R in their human umbilical vein endothelia cells (HUVECs) compared with healthy puerperant women. Similarly, a recent study indicated that overexpression of miR-155 in HUVECs (Zhu et al 2011) suppressed the expression of AT1R via interacting (Xu et al 2008).…”
Section: Mirna Related To Raas In Preeclampsiamentioning
confidence: 95%
“…Cheng and colleagues found that miR-155 was downregulated in the preeclamptic patient endothelial cells. Further study identified another critical preeclamptic pathogenic factor, angiotensin II type 1 receptor, as a target of miR-155 [58]. In addition, miR-155 was linked to the trophoblast function, including proliferation, invasion, and differentiation [59, 60].…”
Section: Placental Micrornamentioning
confidence: 99%
“…Several of the candidates we identified (miR-155-5p, -21-3p, and -223-3p) are highly expressed in a variety of tissues and have been associated with a number of malignant and non-malignant disease states[59], suggesting they might play roles in regulatory pathways common across cell types, including apoptosis, cell-cycle regulation, and response to inflammation. For example, upregulation of miR-155 in both umbilical vein endothelial cells and placenta tissues has been implicated in the pathogenesis of pre-eclampsia, possibly by inhibiting trophoblast invasion and proliferation via the cell-cycle regulator Cyclin D1[60, 61]. miR-155 and -146b, also identified in our study, are induced by inflammatory cytokines, including NF-κB[46, 62, 63].…”
Section: Discussionmentioning
confidence: 76%